Human gene organization driven by the coordination of replication and transcription - Huvet, Maxime; Nicolay, Samuel; Touchon, Marie; Audit, Benjamin; d'Aubenton-Carafa, Yves; Arneodo, Alain; Thermes, Claude

(untitled) (Genome Research, 2007)
In this work, we investigated a large-scale organization of the human genes with respect to putative replication origins. We developed an appropriate multiscale method to analyze the nucleotide compositional skew along the genome and found that in more than one-quarter of the genome, the skew profile presents characteristic patterns consisting of successions of N-shaped structures, designated here N-domains, bordered by putative replication origins. Our analysis of recent experimental timing data confirmed that, in a number of cases, domain borders coincide with replication initiation zones active in the early S phase, whereas the central regions replicate in the late S phase. Around the putative origins, genes are abundant and broadly expressed, and their transcription is co-oriented with replication fork progression. These features weaken progressively with the distance from putative replication origins. At the center of domains, genes are rare and expressed in few tissues. We propose that this specific organization could result from the constraints of accommodating the replication and transcription initiation processes at chromatin level, and reducing head-on collisions between the two machineries. Our findings provide a new model of gene organization in the human genome, which integrates transcription, replication, and chromatin structure as coordinated determinants of genome architecture.